Newborn measles antibody profile in a teaching hospital: Can sex of babies determine measles IgG acquisition from their respective mothers? - Ahmadu, Baba Usman; Yakubu, Mava; Abdullahi, Ibrahim Bello; Pwavimbo, Ambe Jose; Mahmud, Talba Aliyu; Clapton, Difirwiti Harry (Journal of Pediatric Genetics, 2013)
Known sex specific differences in fetal, neonatal morbidity and mortality have been documented. Sex differences also exist in birth-weight centile with males being larger than females at birth. However, these sex differences are not fully explored when studying passive measles immunity acquired by babies from their mothers. Moreover, the mechanisms that confer these sex differences are to a large extent unknown. Therefore, this study assessed sex of babies as a determinant of measles immunoglobulin G acquisition from their respective mothers. One hundred and seventy four newborn babies were enrolled in this study. Enzyme linked immunosorbent assay was used to measure maternal measles antibodies (MMA) from sera collected from these babies at birth. Gestational age of the newborn babies was determined using the Nagele rule, ultrasound scan reports and the Dubowitz criteria. Sex and mean MMA of these babies was compared using the Student’s t test. Significant comparison existed between mean MMA and sex of post term babies (P = 0.000), such that post term males had higher levels of MMA than females. However, overall sex and mean MMA comparison of these babies was not significant (P = 0.977). There were more MMA in male post term babies relative to their female peers; however, overall sex comparison of MMA was not significant. Therefore, there is the need for further study.
Keywords: Maternal measles antibodies; sex; newborn babies; teaching hospital; Nigeria